2022
DOI: 10.1128/aac.01098-21
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Antiparasitic Activity of 10 European Tree Bark Extracts on Toxoplasma gondii and Bioguided Identification of Triterpenes in Alnus glutinosa Barks

Abstract: Toxoplasmosis is a worldwide parasitosis that affects one-third of the population. People at risk, such as immunocompromised patients (AIDS, chemotherapy treatment) or fetuses (maternal-fetal transmission) can develop severe forms of the disease. The antiparasitic activity of extracts of different polarities ( n -heptane, MeOH, MeOH/H 2 O) of ten tree species endemics to temperate regions was investigated against Toxoplasma gondii infectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…After combining the collected fractions on the basis of TLC profile similarities, 16 adjacent fractions (F1, F2 [···] F16) containing simplified mixtures or even pure compounds were obtained (HPTLC fractogram is shown in Figure S3). The major stilbenes were annotated by using a 13 C NMR-based dereplication workflow as explained in Supporting Information. , The resulting heat map after hierarchical clustering analysis on the 13 C chemical shifts highlights four clusters (Figure ). The chemical shifts corresponding to each cluster were submitted as search keys to an in-house developed database that contains more than 5000 compounds to date and associates natural product structures to the predicted 1 H and 13 C NMR chemical shifts calculated by the ACD/Labs predictor.…”
Section: Resultsmentioning
confidence: 99%
“…After combining the collected fractions on the basis of TLC profile similarities, 16 adjacent fractions (F1, F2 [···] F16) containing simplified mixtures or even pure compounds were obtained (HPTLC fractogram is shown in Figure S3). The major stilbenes were annotated by using a 13 C NMR-based dereplication workflow as explained in Supporting Information. , The resulting heat map after hierarchical clustering analysis on the 13 C chemical shifts highlights four clusters (Figure ). The chemical shifts corresponding to each cluster were submitted as search keys to an in-house developed database that contains more than 5000 compounds to date and associates natural product structures to the predicted 1 H and 13 C NMR chemical shifts calculated by the ACD/Labs predictor.…”
Section: Resultsmentioning
confidence: 99%
“…In a previous study [ 9 ], we demonstrated that the n -heptane extract of Alnus glutinosa bark had anti- Toxoplasma gondii activity. A bio-guided fractionation achieved by centrifugal partition chromatography and 13 C NMR-based dereplication showed that the active fractions were mainly composed of lupane-type triterpenes.…”
Section: Discussionmentioning
confidence: 96%
“…In a previous study, we demonstrated the strong anti- T. gondii activity of n -heptane bark extract of black alder ( Alnus glutinosa (L.) Gaertn.) amongst 30 extracts of different polarities from 10 temperate tree species [ 9 ]. The phytochemical study of this extract revealed the majority presence of lupane type triterpenes.…”
Section: Introductionmentioning
confidence: 99%
“…Here are two examples to illustrate this. Betulone is an oxo-derived betulin—plant pentacyclic triterpenoid—that exhibits antitumor, anti-inflammatory, antiparasitic, anticancer, and anti-HIV properties ( Bębenek et al, 2018 ; Kolobova et al, 2019 ; Darme et al, 2022 ). The screening of collection strains showed that growing and resting R. rhodochrous IEGM 66 cells were capable of efficient transformation of up to 3 g/L of the triterpenoid betulin into betulone with a yield of 40–75% ( Grishko et al, 2013 ; Figure 4B ).…”
Section: Biocatalysis Of Active Pharmaceutical Ingredientsmentioning
confidence: 99%